Push-out bond strength of a self-adhesive resin cement used as endodontic sealer - Eduardo Diogo Gurgel-Filho; Felipe Coelho Lima; Vicente de Paula Aragão Saboia; auby de Souza Coutinho-Filho; Aline de Almeida Neves; Emmanuel João Nogueira Leal da Silva (Korean Academy of Conservative Dentistry, 2014)
Objectives The aim of the present study was to investigate the bond strength of RelyX Unicem (3M) to root canal dentin when used as an endodontic sealer. Materials and Methods Samples of 24 single-rooted teeth were prepared with Gates Glidden drills and K3 files. After that, the roots were randomly assigned to three experimental groups (n = 8) according to the filling material, (1) AH Plus (Dentsply De Trey GmbH)/Gutta-Percha cone; (2) Epiphany SE (Pentron)/Resilon cone; (3) RelyX Unicem/Gutta-Percha cone. All roots were filled using a single cone technique associated to vertical condensation. After the filling procedures, each tooth was prepared for a push-out bond strenght test by cutting 1 mm-thick root slices. Loading was performed on a universal testing machine at a speed of 0.5 mm/min. One-way analysis of variance and Tukey test for multiple comparisons were used to compare the results among the experimental groups. Results Epiphany SE/Resilon showed significantly lower push-out bond strength than both AH Plus/Gutta-Percha and RelyX Unicem/Gutta-Percha (p < 0.05). There was no significant difference in bond strength between AH Plus/Gutta-Percha and RelyX Unicem/Gutta-Percha (p > 0.05). Conclusions Under the present in vitro conditions, bond strength to root dentin promoted by RelyX Unicem was similar to AH Plus. Epiphany SE/Resilon resulted in lower bond strength values when compared to both materials.